Micropolítica dos corpos: as drogas como linhas de fugas - Peccioli, Marcelo Romani (2011)
The following dissertation intends to problematize the aesthetics of existence, the ones which have as central element the use of drugs, proposed by the writers Aldous Huxley and William Burroughs. . In order to address the problematization, the research goes back to the threaded discussion of Friedrich Nietzsche, Michel Foucault and Gilles Deleuze especially as a Spinoza reader -, as well as the control devices launched by the State since the disciplinary society s emergence, aiming the bodies docilization. To unfold these two thematic axes experimentation and control -, the research approaches the bodies and by doing a brief report on its dissemination in the urban society and the categorization of the drugs user as an abnormal who requires medical caring and police surveillance. Lastly, the dissertation approaches the works of Aldous Huxley and William Burroughs on the matters regarding drugs, their experiments, creations and confrontations. It is all brought up by the concepts developed by Deleuze and Foucault referencing one s aestheticization